Species Diversity and Paleoecology of Late Pleistocene Horses From Southern Mexico - Jiménez-Hidalgo, Eduardo; Carbot-Chanona, Gerardo; Guerrero-Arenas, Rosalía; Bravo-Cuevas, Victor Manuel; Holdridge, Genevieve Safi; Israde-Alcántara, Isabel (Frontiers in Ecology and Evolution, 2019)
Equids are among the most common mammals found in faunal assemblages of Late Pleistocene age in Mexico. Much of what is known about the Equus species is the result of studies conducted in central and northern Mexico; much less is known about species in lower latitudes of Mexico. Here we describe three species that inhabited Oaxaca and Chiapas states. The fossil localities are in northwestern and central Oaxaca, as well as the central part of Chiapas. In Oaxaca, the largest species, Equus mexicanus, and the medium-sized Equus conversidens are represented by mandibles, skulls, diverse isolated teeth and some postcranial bones, while the smallest species, Haringtonhippus francisci is represented by a skull fragment and few isolated teeth. In Chiapas, E. mexicanus is represented by a mandible and several isolated teeth, E. conversidens by several mandibles and diverse isolated teeth, and H. francisci by isolated teeth and two mandibles. AMS radiocarbon and uranium dating of some of the equid localities in Oaxaca and Chiapas indicate that they were at least present since approximately 44,000 Cal BP years, they were common around 30,000 Cal BP years, and were still present at the end of the Pleistocene, around 12,000 years ago. The record of H. francisci from Chiapas is the youngest in North America. A cluster analysis of extended mesowear data and a discriminant analysis showed that Equus conversidens from Chiapas was obligate grazer, whilst the rest of the equids were variable grazers. Geographic distribution of localities in southern Mexico indicates that during the Pleistocene the equid species moved across the Transvolcanic Belt-Sierra Madre del Sur temperate biogeographic corridor and the Tamaulipas-Central America Gulf Lowlands tropical corridor.